Is the cancer survival improvement in European and American adolescent and young adults still lagging behind that in children?. Issue 1 (19th August 2018) - Trama, Annalisa; Bernasconi, Alice; McCabe, Martin G.; Guevara, Marcela; Gatta, Gemma; Botta, Laura; ,; Ries, Lynn; Bleyer, Archie
Abstract: Improvements during 1978 to 2006 in the 5‐year survival rate of adolescents and young adults (AYAs, age 15–39) and children with cancers common to both age groups were evaluated for 1978 to 2006 in Europe and the USA. AYAs had absolute survival increases of 25% and 15% in Europe and the USA, respectively, but in both cases, AYA 5‐year survival was, as of 2006, 4% lower than those in children. Acute lymphoblastic leukemia (ALL) explained most of the survival difference between AYAs and children on both the continents. In the USA, 20‐ to 39‐year‐olds with ALL have had less survival improvement than those in Europe.